Predicting Students Academic Achievement based on Academic Persistence and Academic Flow - Samira Habibi; Mahin Hatam Vand; Nasim Nayeb darban (Iranian Journal of Educational Research)
Objective: The identification of the determinants and variables influencing academic performance has consistently represented a focal point of inquiry for professionals within the realms of education and training; consequently, the current investigation was undertaken to examine the influence of academic persistence and academic flow in forecasting students' academic success. Methods: This research was characterized as descriptive-correlational, with the study population consisting of all sixth-grade female students residing in District 2 of Tehran in the year 2023, from which 100 eligible participants were selected through convenience sampling methods. The participants responded to the Howard and Crayne Multidimensional Persistence Scale, the Martin and Jackson Academic Flow Scale, and the Dortaj Academic Achievement Questionnaire. Data analysis was conducted employing the Pearson correlation coefficient test and multiple regression techniques. Results: The findings indicated a positive and statistically significant correlation between academic persistence and academic flow concerning academic achievement, with academic persistence and academic engagement accounting for approximately 0.57 of the variances observed in academic success (P<0.01). Conclusions: The implications of this study underscore the critical significance of academic persistence and academic flow in enhancing students' academic performance.